Effect of Agricultural Economics of Community in Advance and Afterward Resident Movement of Hongsa Electric Power’s Project (Case study Nakeankham village, Hongsa district, Sayaboury province) - SITTHIVOHANE , Insavai; PHOUTHAXAY , Phonesavanh; SOULIYAPHUKDEE , Phouvong (Souphanouvong University Journal Multidisciplinary Research and Development, 2019)
Data collection of agricultural economics previous and latter time of Hongsa electric power project construction that has effected to Nakenkham village, Hongsa district, Sayaboury province. The purpose of this study was to research the agricultural economics of effective farmers in between before and after the project construction. It was spent 2 months and the total of 120 household were interviewed. From the result of interview and data collection for analysis, it was shown that the total family’s member in estimated was 4 people. These families had the labors with 2-3 people. The farmer who was mainly interviewed carry out the secondary educational background (training course) and there were 304 people or equal 62.80 %, aged between 20-45 years old and the average monthly income was 1.500.000-2.000.000 kip (After village transposition). The agricultural economics of farmers in Nakenkham village 120 households were decreased when comparing with in advance of project establishment, this reason we can observed from the income of selling agricultural productions, which includes agronomy and animal husbandry, before village had moved the beneficial from animal husbandry was 1.910.200.000 kip/year, agronomy was 1.032.075.000 kip/year. Nevertheless, after village had moved the animal husbandry income was got only 467.800.000 kip/year and Agronomy 112.230.000 kip/year. However, in the recent day, when farmers were evaluated, they had high income but after resident movement the agricultural cultivation were decreased, Because of community has these following strengthen, problem and threaten, before changed the resident, they had positive factors such as larger plentiful area to work on agriculture, better productivity, natural richness, almost people lives under farmer occupation, this reasonable can show that the main income was begun from agricultural activities, whereas, the problem of moving resident was not many option for their occupation and lacking of technical knowledge extension. Whatever, when village has moved they was received the better knowledge and skills in agricultural production techniques from academic extension, the refreshment area from the project, and the main job of worker was project’s laborer because of they had earned better income, the challenge of after moving village was not enough laborer, the area was limitation and not suitable for agricultural cultivation and production, it was showed that the land use was decreased and they also had other choice to work.